Genetic diversity of root-infesting woolly apple aphid Eriosoma lanigerum (Hausmann) (Hemiptera: Aphididae) populations in the Western Cape - Timm, Alicia (Alicia Eva) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2003.